2014
DOI: 10.1016/j.ajpath.2014.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial NLRP3 Inflammasome Activation and Enhanced Neointima Formation in Mice by Adipokine Visfatin

Abstract: Inflammasomes serve as an intracellular machinery to initiate inflammatory response to various danger signals. The present study tested whether an inflammasome centered on nucleotide oligomerization domain-like receptor protein 3 (NLRP3) triggers endothelial inflammatory response to adipokine visfatin, a major injurious adipokine during obesity. NLRP3 inflammasome components were abundantly expressed in cultured mouse microvascular endothelial cells, including NLRP3, apoptosis-associated speck-like protein, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
88
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 50 publications
5
88
1
Order By: Relevance
“…However, Nlrp3 gene deletion significantly reversed the cholesterol crystal-induced inhibition of NO production. This inhibitory action of cholesterol crystals is similar to that of visfatin, a known adipokine that produces ROS-dependent impairment on endothelial function and Nlrp3 inflammasome activation (44,46). Together, these data suggest that Nlrp3-dependent downregulation of eNOS activity is another contributing mechanism that is responsible for cholesterol crystal-induced decreases in NO bioavailability and subsequent endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…However, Nlrp3 gene deletion significantly reversed the cholesterol crystal-induced inhibition of NO production. This inhibitory action of cholesterol crystals is similar to that of visfatin, a known adipokine that produces ROS-dependent impairment on endothelial function and Nlrp3 inflammasome activation (44,46). Together, these data suggest that Nlrp3-dependent downregulation of eNOS activity is another contributing mechanism that is responsible for cholesterol crystal-induced decreases in NO bioavailability and subsequent endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 50%
“…NADPH oxidase-derived ROS associated with ceramide-enriched membrane raft clustering (21,47,52) were found to primarily contribute to the death factor or adipokine visfatin-mediated endothelial dysfunction (13,17,46,48,52,53). We recently demonstrated that ROS is able to activate Nlrp3 inflammasomes in ECs (44). In this study, cholesterol crystals markedly increased endothelial O 2 -production; however, such O 2 -production was not affected by Nlrp3 gene silencing.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Both protective and adverse effects of NLRP3 have been shown in age-related macular degeneration, an eye condition with choroidal neovascularization (20,21). Excessive activation of NLRP3 in ECs by dyslipidemia, disturbed flow, and visfatin may contribute to the development of atherosclerosis and restenosis (22,23). In addition to NLRP3, other PPRs, including TLR-2, TLR-3, TLR-4, TLR-9, NOD1, and NLRP1, are also induced by PXR.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 For in vivo caspase-1 inhibition we used Z-WEHD-FMK (R&D Systems, 1 mg/kg body wt, ip, daily for 6 weeks) and for caspase-4/5 inhibition we used Ac-LEVD-CHO (Enzo Life Sciences, 1 mg/kg body wt, ip, daily for 6 weeks). 33 Caspase-1 and Caspase-3/7 Activity Assay…”
Section: In Vivo Intervention Studiesmentioning
confidence: 99%